Trajetória recente dos indicadores de inovaç\~ao no Brasil - Luiz Ricardo Cavalcante; Fernanda De Negri (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The aim of this paper is to analyze the recent path followed by the innovation indicators in Brazil based on the data available in the four editions of the Brazilian Innovation Survey (PINTEC) issued by the Brazilian Institute of Geography and Statistics (IBGE). Based on the aggregation of the 32 sectors that compose the manufacturing industry into four groups according to their technological intensity (high, medium-high, medium-low and low technology), we also analyze the reasons that explain Brazil's relatively low performance as regards the ratio between R&D expenditures and turnover. The paper is based upon a theoretical discussion on the potentials and constraints of innovation indicators and, in particular, of innovation surveys. From a methodological point of view, the paper is based upon the systematization and analysis of the main descriptive statistics of innovation indicators in Brazil. The main conclusions of this paper are i) the percentage of innovative firms in the industrial sector grew in a systematic way throughout the four editions of the PINTEC, raising from 31.52%, in the period 1998-2000, to 38.11%, in the period 2005-2008; ii) the ratio between private R&D expenditures and GDP reached 0.53% in 2008 (against 0.49% in 2005); iii) there was a significant growth of the relationship between internal and external R&D expenditures and turnover of the industrial sector, which went from 0.65% in 2005 to 0.73% in 2008 - or 0.75% if the analysis is limited to the manufacturing industry; iv) the growth of the technological intensity and the reduction of the number of industrial firms which had R&D expenditures suggest a concentration of R&D activities in a number proportionally smaller of firms; v) mediumhigh technology sectors are those that contribute more for the total R&D expenditures of the manufacturing industry in Brazil (0.37% in 0.75%); and vi) low technology sectors, on the other hand, even though they represent a little less than one third of the turnover of the whole set, contributed with only 0.08 p.p. for the average of the manufacturing industry. After this analysis, we interpose alternatives to increase the ratio between R&D expenditures and turnover in Brazil based on i) the expansion of the technological efforts of the companies that operate in Brazil, especially in the sectors of high and medium-high technological intensity; and ii) changes in the structure of the Brazilian industry.
Keywords: O3; O33; O38; 330; Innovation; Brasilien